Answered

Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Our Q&A platform offers a seamless experience for finding reliable answers from experts in various disciplines. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

Complete these ordered pairs for the equation: y = 3x - 6 (0,__), (__,0), (1,__)

Sagot :

Lilith
[tex]y = 3x - 6 \\ \\ (0, ....), \\\\ x=0\\\\y=3\cdot 0-6=-6\\\\(0,-6)[/tex]



[tex](.... ,0),\\\\ y=0\\ \\0=3x-6 \\ \\3x=6\ \ /:3\\\\x=2 \\\\(2,0)[/tex]



[tex](1, ....), \\\\ x=1\\\\y=3\cdot 1-6=3-6=-3\\\\(0,-3)[/tex]